Tips for turtles: how to improve success when rehabilitating turtles - Carstairs, Sue (Wildlife Rehabilitation Bulletin, 2025)
Turtles are among the most endangered vertebrates on the planet. While they face many threats, road mortality is one of the main causes for population declines in North America. Due to their life history (extremely long lives, slow maturity and low recruitment into the adult population), adults lost on the roads are impossible to replace in the population. As a result, treatment and rehabilitation of adult turtles is unique in its conservation impact. Turtles are very different than mammals and birds in their response to medical treatment, but their rehabilitation can be very rewarding. This paper outlines some simple approaches to their care that can increase success for rehabilitation of these species.